2017
DOI: 10.5937/ekonomika1702015a
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' attitude on locally madetextiles and its impact on job creation: The Nigerian experience

Abstract: This study examined consumers' attitude on Made-in-Nigeria textiles and its impact on Job creation in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Numerous studies that examined the link between attitude and purchasing intention concluded that attitude is a critical factor in predicting consumers' purchasing intentions [45,46]. Purchase intention and attitude are favorably and directly correlated [17,47]. Attitude does not always have a signifcant efect on purchasing intention because various situational factors might infuence actual purchase decisions [48,49].…”
Section: Determinants Of Purchasing Intention Towards Localmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies that examined the link between attitude and purchasing intention concluded that attitude is a critical factor in predicting consumers' purchasing intentions [45,46]. Purchase intention and attitude are favorably and directly correlated [17,47]. Attitude does not always have a signifcant efect on purchasing intention because various situational factors might infuence actual purchase decisions [48,49].…”
Section: Determinants Of Purchasing Intention Towards Localmentioning
confidence: 99%
“…Consequently, this study intended to explore the determinants of Ethiopian consumers' purchasing behavior towards locally produced apparel products. Consumer behavior has been studied in "developed nations" [14][15][16] and other developing countries [17][18][19][20], but there are a limited number of studies and published papers regarding Ethiopian consumers' purchasing behavior towards apparel products during purchasing or use [21]. Te study incorporates product attributes and consumer ethnocentrism into the theory of planned behavior (TPB) model to examine their impact on consumers' purchasing intentions which are rarely studied in such a combination.…”
Section: Introductionmentioning
confidence: 99%